Practical algorithms for image analysis - Seul, M; O'Gorman, L; Sammon, M. J (Cambridge University Press, 2000)
This book offers guided access to a collection of algorithms for the digital manipulation and analysis of images. Written in classic \"cookbook\" style, it reflects the authors\' long experience as users and developers of image analysis algorithms and software. For each task, they present a description and implementation of the most suitable procedure in easy-to-use form. The algorithms range from the simplest steps to advanced functions not commonly available for Windows users. Each self-contained section treats a single operation (histogram evaluation, low-pass filtering, and edge detection, among others). The coverage includes typical situations requiring that operation and then discusses the algorithm and implementation. Sections start with a header illustrating the nature of the procedure through a \"before\" and \"after\" pictorial example and a ready-reference that lists typical applications, keywords, and related procedures. Annotated references can be found at the end of each section. An accompanying CD-ROM contains a collection of C programs for carrying out the book\'s procedures.
Keywords: radiologie, nukleární medicína a zobrazovací metody